Studium luminiscenčních vlastností organických polovodičů - Koňák, Petr (Vysoké učení technické v Brně. Fakulta elektrotechniky a komunikačních technologií, 2009)
Práce se zabývá využitím organických polovodičů k elektroluminiscenci. V úvodu práce je rozebrána problematika organických polovodičů, jejich struktur a dnešní využití. Dále se zabývá dodanými vzorky, jejich chemickým složením a taktéž zahrnuje výsledky z měření elektoluminiscence.

This document describes using organic semiconductors to the electroluminescence on thin layers. In introduction of this file there is analysis a the problem of organic semiconductors and it's using in today's world. Next, I want to describe work with the given samples, their chemical composition and also include results from the measuration of electroluminescence.
Study of luminicsence properties of organic semicondustors
Keywords: Aktivní matice; pasivní matice; dispej; vrstva; struktura; světlo; citlivost.; Active Matrix; Passive Matrix; Display; layer; structure; light; sensitivity